2022
DOI: 10.3892/etm.2022.11556
|View full text |Cite
|
Sign up to set email alerts
|

Application of alkaline phosphatase‑to‑platelet ratio as a novel noninvasive index predicts liver fibrosis in patients with chronic hepatitis B

Abstract: Assessment of the extent of liver fibrosis is a crucial requirement for the design of antiviral treatments for patients with chronic hepatitis B (CHB). Several non-invasive predictive indices have been developed as potential alternatives to liver biopsy for fibrosis assessment. The present study aimed to establish a novel non-invasive method for predicting liver fibrosis in patients with CHB. A total of 382 patients with CHB who underwent liver biopsy and pathological examination at The Second Hospital of Anhu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…[ 21 ] In this study, APPR was found to be significantly positively correlated with APRI and FIB-4. Analogous to our research results, Pan et al [ 15 ] found that APPR was positively correlated with APRI and FIB-4, as well as with the stage of hepatic fibrosis. It was a significant independent predictor of hepatic fibrosis and could be used to evaluate hepatic fibrosis in patients with CHB.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[ 21 ] In this study, APPR was found to be significantly positively correlated with APRI and FIB-4. Analogous to our research results, Pan et al [ 15 ] found that APPR was positively correlated with APRI and FIB-4, as well as with the stage of hepatic fibrosis. It was a significant independent predictor of hepatic fibrosis and could be used to evaluate hepatic fibrosis in patients with CHB.…”
Section: Discussionsupporting
confidence: 91%
“…[14] APPR was utilized to evaluate the prognosis of patients with HCC and CHB. [15,16] In the current study, our results revealed that increased MHR and APPR were strongly associated with the deterioration of PBC patients, and suggested that the combination of MHR with APPR might hold a significant diagnostic value in distinguishing PBC from AIH and CHB. In addition, we found that APPR may be a noninvasive indicator of hepatic fibrosis in PBC.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Концентрация аминотрансфераз (АЛТ, АСТ) во время лечения коррелирует с долгосрочной выживаемостью пациентов с АИГ I типа [6]. Описано применение отношения щелочной фосфатазы (ЩФ) к тром-боцитам в качестве неинвазивного показателя для прогнозирования стадии ФП у пациентов с хроническим гепатитом В [7]. Обсуждается применения новых биомаркеров, которые могут быть клинически значимыми в отношении дифференцировки различных стадий ФП, активности процесса и эффективности лечения заболевания [8].…”
Section: Introductionunclassified